2014
DOI: 10.3906/vet-1404-57
|View full text |Cite
|
Sign up to set email alerts
|

Application of dietary fish oil in dairy cow reproduction

Abstract: Feed fats are commonly used as a component of high-yielding cow diet rations. Many studies have been conducted on the effects of fat supplementation on metabolism, milk composition, and improvements in dairy cow reproduction. The positive effects on fat (vegetable oil) and energy supplementation on improvements in reproduction are well documented. Consumption of polyunsaturated fatty acids (PUFAs), including n-3 acids, in appropriate feed doses improves fertility of dairy cows. A fat source with high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…İt is thought that omega 3 polyunsaturated fatty acids improved the synthesis of prostaglandins by acting on the endocrine system and improve fertility functions by affecting positively on the development of eggs and embryos. This study results in agreement with Zwyrzykowska and Kupczyñskı (2014) and Ambrose et al (2006). In addition, results of Hutchinsona et al (2012) in the Afshari sheep were similar to those of this study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…İt is thought that omega 3 polyunsaturated fatty acids improved the synthesis of prostaglandins by acting on the endocrine system and improve fertility functions by affecting positively on the development of eggs and embryos. This study results in agreement with Zwyrzykowska and Kupczyñskı (2014) and Ambrose et al (2006). In addition, results of Hutchinsona et al (2012) in the Afshari sheep were similar to those of this study.…”
Section: Resultssupporting
confidence: 92%
“…Although the addition of fatty acids to rations affects fertility in the positive direction in ruminant, this mechanism has not yet been clearly identified (Hutchinsona et al, 2012). It has also been reported that knowledge of the effects of by pass omega-3 fatty acids on reproductive performance in sheep during the flushing stage is very limited (Zwyrzykowska and Kupczyñskı, 2014). On the other hand, gonadotropins are mainly used for ovarian stimulation in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…It has a positive effect on the quality of male semen [ 8 , 9 , 10 ]. It can elongate and add new double bonds and thus convert into eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) ( Figure 1 ) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%